A Case Study on Oncocytic Carcinoma with Liver Metastasis: Unusual Treatment Strategies and Clinical Insights - Hourani, Mohammad; Giridharan, Selvaraj; Azribi, Fathi; Ansari, Hidayath; Ansari, Jawaher (Medicine and Medical Research: New Perspectives Vol. 1, 2024)
Oncocytic tumors are a diverse group of neoplasms that can affect various organs. These tumors are characterized by oncocytes, cells exhibiting abnormal mitochondrial accumulation. This chapter reports a distinctive case of malignant oncocytic carcinoma originating in the pancreas, an organ rarely associated with such tumors. The diagnostic journey highlights the tumor’s resemblance to renal cell carcinoma but without renal involvement. A significant aspect of this case is the successful and sustained response to combined immunotherapy and tyrosine kinase inhibitors, demonstrating a potential therapeutic pathway for similar rare cases. Surgical removal remains the preferred treatment for resectable lesions. This study contributes to a deeper understanding of pancreatic oncocytic tumors and their management. This case underscores the need for further research to better understand this rare condition, classify metastatic risks, and develop tailored treatments.